When Theory meets Practice in Entanglements of Ageing and Technology - Michela Cozza; Britt Östlund; Alexander Peine (Tecnoscienza, 2021)
This special issue contributes to the new academic field known as Socio-gerontechnology, which has emerged at the cross-section of STS and Age Studies. All contributions published in the following pages explore what happens when theories meet practice in the relation between ageing and technology, by pointing out the role of design(ers) in configuring and reconfiguring such a relation. In line with the so-called “engaged program” in STS, these articles address different topics of political importance and pragmatic relevance. Indeed, they share the critique of ageist images that underlie public and specialist discourses around ageing and technology. By combining the emancipatory thrive of critical studies of age and ageing and the nuanced STS approach to the study of the entanglements of ageing and technology, this special issue offers a collection of theoretical elaborations and methodological considerations developed along with empirical analyses. Overall, they explore the practical politics of technology, within the growing field of Socio-gerontechnology.